Patient Satisfaction Level With The Use Of The Mobile JKN Application For Outpatient Registration At Bhayangkara Hospital Denpasar - Ni Putu Amiyanti; Nurul Faidah; Ika Setya Purwanti (International Journal of Health Engineering and Technology, 2026)
In an effort to improve healthcare services, the Mobile JKN application was introduced to facilitate patients in accessing registration and various healthcare facility services. Evaluation is necessary to determine the level of user satisfaction with the Mobile JKN application. One method that can be used to measure user satisfaction is the SERVQUAL method, which measures service quality based on users’ perceptions and expectations of the services provided. This study used a descriptive method with a quantitative approach. The sample consisted of 85 respondents selected using a simple random sampling technique. The research instrument was a Likert scale questionnaire based on the five SERVQUAL dimensions, namely tangible, reliability, responsiveness, assurance, and empathy. Data were analyzed descriptively to determine the level of patient satisfaction with the services provided. The results showed that the level of patient satisfaction was categorized as very satisfied. The highest score was found in the tangible dimension with a Patient Satisfaction Index (PSI) of 91%, while the lowest score was in the responsiveness dimension with a PSI of 84%. The reliability dimension obtained a PSI of 87%, the assurance dimension 86%, and the empathy dimension 86%. These findings indicate that the application has facilitated the registration process; however, several aspects still need improvement, particularly in responsiveness and the speed of service within the application.